Exploring the Integration of Climate Change Education: Teachers’ Perspectives from P5 Projects and English Lessons in Secondary School - Sary Silvhiany; Salsabila Nurhaliza; Muhaimin; Malihah Putri Jasmine (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
The integration of climate change education is the primary focus of initiatives to raise student awareness and knowledge about climate change in many nations, including Indonesia. The integration of climate change education in Palembang secondary schools is the subject of this study, which focuses on the opinions of English teachers who are teaching English classes and participating in the P5 project (Pancasila Student Profile Strengthening Project). The purpose of this study is to determine how much climate change education is included in these projects and lessons, as well as how comfortable and eager the teachers are to use these ideas in their instruction. The design of the research is qualitative research design. The study employed theme analysis and semi- structured interviews with four English teachers to investigate the opportunities and problems of integrating climate change education. Despite the P5 project initiative, the results show a gap in the complete integration of climate change into English education. The necessity of formal training and resources to properly teach climate change was acknowledged by teachers, underscoring the significance of resolving these issues for the successful adoption of climate change teaching in secondary schools.